Pemanfaatan Media Digital Terhadap Minat Belajar Mengaji Pada Peserta Didik - Ilma Nurwahidah; Nada Nupus Ihwani; Nadila Sofia; Riska Riska (-, 2022)
The development of technology is currently very fast and spreads in everyday life. Utilization of technology is also used in the teaching and learning process for both teachers and students in schools. The purpose of this study is to find out what innovations can be done to deal with the lack of interest in learning the Koran in elementary school children. This type of research method is carried out using a literature study method sourced from articles, books and online journals related to the title of the study. The method used in this research is to do a literature review by reading a lot of journals that do the same research, by reading a lot it will deepen the research that will be started. The results of the study can be concluded that learning media can increase and direct children's attention so that it can lead to learning motivation, more direct interaction between students and their environment, and the possibility of students to learn independently according to their abilities and interests. The media used in learning can make it easier for children and increase their motivation or fondness for reciting children, that is, they can use digital media, but in using digital media they must be accompanied and supported by parents so that children can learn to recite the Koran in a directed and understandable way.